Search for Lorentz invariance and CPT violation with muon antineutrinos in the MINOS Near Detector - Adamson, P; Ayres, D; Barr, G; Bishai, M; Blake, A; Bock, G; Boehnlein, D; Bogert, D; Cao, S; Cavanaugh, S; Childress, S; Coelho, J; et al. (2012)
We have searched for sidereal variations in the rate of antineutrino interactions in the MINOS Near Detector. Using antineutrinos produced by the NuMI beam, we find no statistically significant sidereal modulation in the rate. When this result is placed in the context of the Standard Model Extension theory we are able to place upper limits on the coefficients defining the theory. These limits are used in combination with the results from an earlier analysis of MINOS neutrino data to further constrain the coefficients. © 2012 American Physical Society.